The AppliedMathematical SimulationModeling Algorithm for a Multi Aircraft Landing Dynamic System at Bujumbura International Airport Mathematics and Innovative Technologies in Africa - Nahayo, F.; Ndimubandi, J.; Manirabona, A.; Niyongere, A. (European Scientific Journal, ESJ, 2019)
The aim of this paper is to set up an efficient nonlinear application algorithm simulation model for a multi aircraft landing dynamic system in one Runway when considering Bujumbura International Airport. The mathematical modelization of the solved problem is a non-convex optimal control governed by ordinary non-linear differential equations.The dynamic programming technic is applied because it is a sufficiently high order and it does-not require computation of the partial derivatives of the aircraft dynamic. This application is be coded with Linux operating system, but it can also be run on the windows system. High runing performance are obtained with results giving feasible trajectories with a robust optimizing of the objective function. The user interfaces designed in Glade are saved as XML, and by using the GtkBuilder GTK+ object these can be loaded by applications dynamically as needed. By using GtkBuilder, Glade XML files can be used in numerous programming languages including C, C++, C#, Java, Perl, Python,AMPL,etc.. Glade is Free Software released under the GNU GPL License. The algorithm is implemented when considering discrete mathematics while using Bujumbura International Airport Geographic Information System.